2017
DOI: 10.14814/phy2.13457
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, neuromuscular, and recovery responses to light versus heavy resistance exercise in young men

Abstract: Recent evidence suggests that resistance training with light or heavy loads to failure results in similar adaptations. Herein, we compared how both training modalities affect the molecular, neuromuscular, and recovery responses following exercise. Resistance‐trained males (mean ± SE: 22 ± 2 years, 84.8 ± 9.0 kg, 1.79 ± 0.06 m; n = 15) performed a crossover design of four sets of leg extensor exercise at 30% (light RE) or 80% (heavy RE) one repetition maximum (1RM) to repetition failure, and heavy RE or light R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 71 publications
(182 reference statements)
4
28
0
Order By: Relevance
“…Approximately 48–96 h following T1 and T3, as well as two and one-half weeks into the intervention, participants performed one repetition maximum (1-RM) back squat and power clean assessments using a 20 kg barbell (York Barbell) and free weights at the local CrossFit gymnasium (Backbone CrossFit, Auburn, AL, USA). The demonstration of proper technique as well as the implementation of progressively-loaded RM testing were overseen by Wesley C. Kephart and Coree D. Pledge, who have vast experience with strength and performance testing [ 14 , 15 , 16 ]. A repetition was not counted if subjects exhibited poor and/or unsafe technique or needed assistance with a repetition during maximal testing.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 48–96 h following T1 and T3, as well as two and one-half weeks into the intervention, participants performed one repetition maximum (1-RM) back squat and power clean assessments using a 20 kg barbell (York Barbell) and free weights at the local CrossFit gymnasium (Backbone CrossFit, Auburn, AL, USA). The demonstration of proper technique as well as the implementation of progressively-loaded RM testing were overseen by Wesley C. Kephart and Coree D. Pledge, who have vast experience with strength and performance testing [ 14 , 15 , 16 ]. A repetition was not counted if subjects exhibited poor and/or unsafe technique or needed assistance with a repetition during maximal testing.…”
Section: Methodsmentioning
confidence: 99%
“…Following the POMS questionnaire, pressure-to-pain threshold (PPT) of the outer aspect of the right upper thigh was measured using a handheld algometer (Force Ten FDX, Wagner Instruments, Greenwich, CT, USA) according to methods described in our previous work ( 19 ). Briefly, focal pressure was applied by the algometer to proximal, medial, and distal portions of the right vastus lateralis (VL) which were marked for accurate application of force.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, type II muscle fibre hypertrophy, even when lighter loads are lifted to task failure, is indicative of recurrent type II fibre activation (Mitchell et al 2012;Morton et al 2015Morton et al , 2016. However, on the basis of greater surface electromyography (EMG) amplitude (Jenkins et al 2015;Looney et al 2016;Haun et al 2017) or decomposition of the EMG signal (Muddle et al 2018), other studies have reported that heavier loads are superior to lighter loads in terms of recruiting higher threshold motor units and thus the eventual hypertrophy of type II fibres (Grgic & Schoenfeld, 2018).…”
Section: Introductionmentioning
confidence: 99%